Light-harvesting complexes in photosystem II regulate glutathione-induced sensitivity of Arabidopsis guard cells to abscisic acid - Md. Sarwar, Jahan (Elsevier GmbH, 2016)
Light-harvesting complexes (LHCs) in photosystem II (PSII) regulate glutathione (GSH) functions in plants. To investigate whether LHCs control GSH biosynthesis that modifies guard cell abscisic acid (ABA) sensitivity, we evaluated GSH content, stomatal aperture, reactive oxygen species (ROS), weight loss and plant growth using a ch1-1 mutant that was defective of LHCs and compared this with wild-type (WT) Arabidopsis thaliana plants. Glutathione monoethyl ester (GSHmee) increased but 1-chloro-2,4 dinitrobenzene (CDNB) decreased the GSH content in the guard cells. The guard cells of the ch1-1 mutants accumulated significantly less GSH than the WT plants. The guard cells of the ch1-1 mutants also showed higher sensitivity to ABA than the WT plants. The CDNB treatment increased but the GSHmee treatment decreased the ABA sensitivity of the guard cells without affecting ABA-induced ROS production. Dark and light treatments altered the GSH content and stomatal aperture of the guard cells of ch1-1 and WT plants, irrespective of CDNB and GSHmee. The ch1-1 mutant contained fewer guard cells and displayed poor growth, late flowering and stumpy weight loss compared with the WT plants. This study suggests that defective LHCs reduced the GSH content in the guard cells and increased sensitivity to ABA, resulting in stomatal closure.